Selective extraction and solid state complexation of iron(III) with bis(β-diketone) ligand. (2021) - Narayanan, Remya P.; Palantavida, Shajesh
Abstract: The manufacturing of the white pigment TiO2 through chloride process generates a large amount of acidic solid waste containing multivalent metal ions such as Fe(III), Fe(II), Al(III), Ti(IV), V(V), Cr(III), Mn(II) and Mg (II). The selective extraction possibility of iron(III) using a bis (-diketonate) ligand from the other associated metal ions such as magnesium(II), aluminum(III), titanium(IV), vanadium(V), chromium(III), and manganese(II) in the titania waste chloride liquors has been investigated by using a synthetic waste chloride liquor. An investigation on the complexation of iron(III) with 4-pyridoylbis(1-phenyl-3-methyl-5-pyrazolone) is also presented in this paper. The solid complex of iron(III) with 4-pyridoylbis(1-phenyl-3-methyl-5-pyrazolone) has been prepared and characterized using various spectroscopic techniques. The electronic structure of the ligand and triple helical structure of the complex were calculated using the unrestricted density functional theory (DFT) method.